(untitled) - Czinkota, Michael R. (Fort Worth, 1998)
The book presents the basic concepts of international marketing; discusses the environmental forces that the international marketer has to consider; deals with the various activities necessary for international marketing planning and concentrates on the beginning of international marketing activities. The book also discusses strategy and marketing management issues most relevant to the expanded global operations of multinational corporations. Finally, the book addresses transitions in international marketing
Keywords: International business enterprises,International economic relations,Export marketing,Tiếp thị xuất khẩu,Quan hệ kinh tế quốc tế,Doanh nghiệp kinh doanh quốc tế; Management,Quản lý